Pengaruh Quality of Islamic Services, Harga dan Kepuasan Pelanggan Terhadap Minat Beli Ulang Di Kheyla Mart Kab. Enrekang - Siti hairunnisa; Fathurrahman; A. Syathir Sofyan (Universitas Islam Negeri Alauddin Makassar, 2024)
This study aims to determine the influence of sharia service quality, price and customer satisfaction on repurchase interest at Kheyla Mart. The approach taken in this study is a quantitative approach. The sampling method was based on Morgen's table, the respondents in this study amounted to 278 customers. The data used was taken through the distribution of questionnaires. This study uses SEM analysis techniques using a test tool, namely SMARPLS. The results of the study showed that simultaneously the variables of sharia service quality (X1), price (X2) and customer satisfaction (X3) had an effect on repurchase interest (Y). In particular, each variable of sharia service quality, price and customer satisfaction has a positive and significant effect on repurchase interest at Kheyla Mart.